Exploring the effectiveness of using GeoGebra and e-transformation in teaching and learning mathematics - Abu Bakar, Kamariah; Mohd Ayub, Ahmad Fauzi; Ahmad Tarmizi, Rohani (WSEAS Press, 2010)
The integration of technological tools especially computer softwares has been widely practised in teaching and learning especially in mathematics. Various types of dynamic mathematical softwares, such as Geometer’s Sketchpad, Autograph and the Graphing Calculator, have been utilized for learning mathematics in Malaysian secondary schools. However, the use of an open source software in teaching and learning mathematics is still new in Malaysia. This paper compared the effectiveness of using an open source software i.e. GeoGebra and a courseware developed by the researcher for learning transformation. Purposive sampling was carried out and a total of 70 secondary school students from a school in Malaysia participated in the study. These students were randomly assigned into two separate groups. Each group underwent instruction utilizing either the GeoGebra or the e-transformation software. Findings showed that significant differences existed between the pre and post tests scores of each of the GeoGebra and e-transformation groups. However, there was no significant difference in the performance scores on the post test of both groups. Further analysis also showed there was no significant difference on each topic included in the post test. These findings showed that both computer softwares had been effective in teaching mathematics at Malaysian secondary school level.